A qualitative exploration of the uses of the International Classification of Functioning, Disability and Health at an inpatient neurorehabilitation facility in the Western Cape, South Africa - Hall, Rehan (Stellenbosch : Stellenbosch University, 2019)
Thesis (MHumanRehabSt)--Stellenbosch University, 2019.